ANALYSIS OF THE IMPACT OF INTEGRATING SUSTAINABILITY REPORTING INTO TRADITIONAL FINANCIAL STATEMENTS - Ishe Yudiwati; Nurhastuty Kesumo Wardhani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
This study examines the increasing importance of integrating sustainability considerations into corporate governance and reporting practices. As global business environments continue to evolve, companies are required not only to focus on financial performance but also to address the social and environmental impacts of their operations. In response to growing stakeholder demands for sustainability transparency, the establishment of sustainability committees has emerged as a key governance mechanism to enhance the credibility and quality of sustainability reporting. However, in practice, the function of sustainability committees often remains separated from traditional financial reporting processes, potentially creating information gaps that may impair decision-making quality. This study aims to analyze the impact of integrating sustainability committees into traditional financial reporting on information quality, stakeholder perceptions and trust, and overall company performance. A quantitative approach is employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among variables, including the mediating roles of information quality and stakeholder perceptions. The literature suggests that stronger sustainability governance through such integration improves the relevance, reliability, and completeness of corporate disclosures. In addition, sustainability committees contribute to more positive stakeholder perceptions, which in turn enhance firm performance and value. The proposed conceptual model posits that the integration of sustainability committees positively influences information quality and stakeholder perceptions, which subsequently affect company performance, both directly and indirectly. This study contributes to the development of integrated sustainability reporting literature and provides practical implications for companies and regulators in strengthening accountability and transparency, particularly in the Indonesian context.